Increasing follow-up questionnaire response rates in a randomized controlled trial of telehealth for depression: three embedded controlled studies - Edwards, Louisa; Salisbury, Chris; Horspool, Kimberley; Foster, Alexis; Garner, Katy; Montgomery, Alan A. (BioMed Central, 2016)
Background: Attrition is problematic in trials, and may be exacerbated in longer studies, telehealth trials and participants with depression – three features of The Healthlines Study. Advance notification, including a photograph and using action-oriented email subject lines might increase response rates, but require further investigation. We examined the effectiveness of these interventions in three embedded Healthlines studies. Methods: Based in different trial sites, participants with depression were alternately allocated to be pre-called or not ahead of the 8-month follow-up questionnaire (Study 1), randomized to receive a research team photograph or not with their 12-month questionnaire (Study 2), and randomized to receive an action-oriented (‘ACTION REQUIRED’) or standard (‘Questionnaire reminder’) 12-month email reminder (Study 3). Participants could complete online or postal questionnaires, and received up to five questionnaire reminders. The primary outcome was completion of the Patient Health Questionnaire (PHQ-9). Secondary outcome measures were the number of reminders and time to questionnaire completion. Results: Of a total of 609 Healthlines depression participants, 190, 251 and 231 participants were included in Studies 1–3 (intervention: 95, 126 and 115), respectively. Outcome completion was ≥90 % across studies, with no differences between trial arms (Study 1: OR 0.38, 95 % CI 0.07–2.10; Study 2: OR 0.84, 95 % CI 0.26–2.66; Study 3: OR 0.53 95 % CI 0.19–1.49). Pre-called participants were less likely to require a reminder (48.4 % vs 62.1 %, OR 0.41, 95 % CI 0.21–0.78), required fewer reminders (adjusted difference in means −0.67, 95 % CI −1.13 to −0.20), and completed follow-up quicker (median 8 vs 15 days, HR 1.35, 95 % CI 1.00–1.82) than control subjects. There were no significant between-group differences in Studies 2 or 3. Conclusions: Eventual response rates in this trial were high, with no further improvement from these interventions. While the photograph and email interventions were ineffective, pre-calling participants reduced time to completion. This strategy might be helpful when the timing of study completion is important. Researchers perceived a substantial benefit from the reduction in reminders with pre-calling, despite no overall decrease in net effort after accounting for pre-notification.